1997
DOI: 10.1046/j.1365-2982.1997.d01-25.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic migrating motor complexes (CMMCs) in the isolated mouse colon

Abstract: Spontaneous contractions were recorded from the circular muscle layer at three sites along the isolated mouse colon. The interval between contractions was approximately 4.5 min. The mean duration of the contractions ranged from 26 sec in the distal colon to 45 sec in the proximal colon. Contractions migrating more than half the length of the colon were termed colonic migrating motor complexes (CMMCs). Over 90% of tissues demonstrated migration predominantly in an aboral direction. Hyoscine (10(-6) M) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
161
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(186 citation statements)
references
References 15 publications
24
161
1
Order By: Relevance
“…12 The present study deals with propulsive motor patterns in the rat colon. Colonic propulsive contractions are often referred to as "colonic migrating motor complexes (CMMCs)" described as such in the rat 13,14 and mouse [15][16][17] colon. We and others recently reported that the CMMC contains 2 distinct propulsive motor patterns, a pancolonic long distance contraction (LDC) and a rhythmic propagating motor complex (RPMC) that is primarily observed in the mid and distal colon.…”
Section: Introductionmentioning
confidence: 99%
“…12 The present study deals with propulsive motor patterns in the rat colon. Colonic propulsive contractions are often referred to as "colonic migrating motor complexes (CMMCs)" described as such in the rat 13,14 and mouse [15][16][17] colon. We and others recently reported that the CMMC contains 2 distinct propulsive motor patterns, a pancolonic long distance contraction (LDC) and a rhythmic propagating motor complex (RPMC) that is primarily observed in the mid and distal colon.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent developments allow some conclusions to be drawn. Isolated mouse intestine and colon exhibit periodic strong contraction complexes that propagate along the segment in a manner analogous to phase III contractions of interdigestive MMCs [132][133][134][135]. This similarity is so strong that the colonic propagating contraction complexes are usually termed colonic MMCs, although they may actually be analogues of mass-movement contractions involved in defecation.…”
Section: Functional Roles Of Purinergic Ijpsmentioning
confidence: 99%
“…22 This toxin abolishes CMMCs generated by enteric motor nerve activity. 23 We found that TTX mimicked the functional effects of narcoleptic IgG in this isolated organ preparation. Our results are consistent with a model in which an Ab in patients with narcolepsy blocks neurotransmission of both excitatory and inhibitory enteric motor nerves.…”
mentioning
confidence: 91%
“…23 Therefore, we investigated whether TTX could mimic the actions of the narcoleptic IgG. In colonic preparations undergoing CMMC activity, addition of 0.6 mmol/l TTX abolished CMMCs and increased smooth muscle resting tension (Figure 4a).…”
Section: Ttx Mimics the Effect Of Narcoleptic Iggmentioning
confidence: 99%
See 1 more Smart Citation